The Interplay of Compensation and Working Facilities on Local Tax Revenue: A Data Panel Evidence of Municipalities in East Borneo - Ramadhani, Muhammad Harits Zidni Khatib; Mahardika, Swadia Gandhi; Rahmah, Asmadhini Handayani (Eastasouth Institute, 2024)
This study investigates the relationship between employee compensation, working facilities, and local tax revenue generation in East Kalimantan Province, Indonesia. Utilizing panel data multiple linear regression analysis, the research analyzes financial reports from ten Regencies and Cities (Balikpapan, Samarinda, Bontang, Kutai Timur, Kutai Barat, Kutai Kartanegara, Penajam Paser Utara, Berau, Mahakam Ulu, and Paser) over the period of 2017-2023. Employee compensation, represented by growth of employee expenditures (PBP), captures the year-to-year increase in personnel costs. Working facilities, represented by growth of goods and service expenditures (PBBJ), reflect the year-to-year change in spending on operational resources. The findings reveal a positive association between both growth in employee expenditures and growth in goods and services expenditures with local tax revenue, but these relationships are not statistically significant. This suggests that factors beyond employee compensation and working facilities likely play a more prominent role in driving regional tax revenue growth.